The efficacy of predatory fungi on the control of gastrointestinal parasites in domestic and wild animals—A systematic review - Canhão-Dias, M.; Paz-Silva, A.; Madeira de Carvalho, L.M. (Veterinary parasitology, 2020)
•Systematic review delivering robust evidence on Biological Control of parasites.•New insights on the efficacy of predatory fungi.•New fungi products as promising tools for gastrointestinal parasite control. Gastrointestinal parasites like nematodes are associated with significant impacts on animal health, causing poor growth rates, diseases and even death. Traditional parasite control includes the use of anthelmintic drugs, albeit being associated with drug resistance and ecotoxicity. In the last decade, biological control of parasites using nematophagous or predatory fungi has been increasingly studied, although systematic evidence of its efficacy is still lacking. The aim of this work was to assess the evidence of efficacy of nematophagous fungi in the control of nematodes and other gastrointestinal parasites in different animal species. Using the PICO method (Population, Intervention, Comparison and Outcomes), we performed a systematic review on the subject to search for original papers published between January 2006 and October 2019, written in English, and indexed in PubMed/Medline. Medical Subject Headings (MeSH) terms were used in the syntax. Papers were selected for detailed review based on title and abstract. Inclusion and exclusion criteria were applied, and relevant data were collected from the remaining papers. The literature search retrieved 616 papers. Eighty-nine were submitted to a detailed review. In the end, 53 papers were included in the analysis. The studies were very heterogeneous, using different fungi, doses, frequency of administration, duration of treatment, host animals, and target parasites. Considering the 53 papers, 44 studies (83 % of the interventions) showed efficacy, with only 9 studies (17 %) showing no significant differences when compared to control. With the increasing hazards of drug resistance and ecotoxicity, biological control with predatory fungi stands out as a good tool for future parasite management, whether as a complementary treatment or as an alternative to standard parasite control.